Competition and regulation as a means of reducing CO2 emissions: Experience from U.S. fossil fuel power plants - Christian Growitsch; Simon Paulus; Heike Wetzel (Philipps-University Marburg, School of Business and Economics, 2017)
Levels of CO2 emissions from electricity generation in the U.S. have changed considerably in the last decade. This development can be attributed to two factors. First, the shale gas revolution has reduced gas prices significantly, leading to a crowding out of the more CO2-intensive coal for electricity generation. Secondly, environmental regulations have been tightened at both the federal and the state level. In this article, we analyze the relative CO2 emission performance across 48 states in the U.S. using a two-stage empirical approach. In the first stage, we identify the states that followed best practice between 2000 and 2013, by applying nonparametric benchmarking techniques. In the second stage, we regress our CO2 emission performance indicators on the state-specific national gas prices, the states' CO2 regulatory policies and a number of other state-specific factors in order to identify the main drivers of the developments. We find that the CO2 emission performance improved on average by 15% across all states from 2000 to 2013. Furthermore, our second-stage results support the argument that decreasing natural gas prices and stringent regulatory measures, such as cap-and-trade programs, have a positive impact on the state-specific CO2 emission performance.
Keywords: C61; D24; L94; Q58; 330; carbon dioxide emission performance; data envelopment analysis; global Malmquist index; environmental regulation